Professional preferences of students in physical education and sport sciences - Jerónimo García Fernández; Francisco Pires Vega; Jesús Fernández Gavira (FEADEF, 2013)
The actual context has enhanced job opportunities in the field of sport in order to respond to the current market demand. Thus, Physical Education and Sport Science graduates who begin to do differents jobs to the traditional ones but relate to their study field. The aim of this study was to guess which are the job preferences of the students of Physical Education and Sport Science of Seville University by gender and age doing the second cycle of their college degree and determine if there are significant differences. A descriptive analysis was carried out, using a questionnaire based on several researches, it was related to professional opportunities in sport sciences. The sample was of 118 students which represented 40.7% of the overall registered students. Results shown that sport management is the most preferable professional opportunity for women and men of the total sample, following in second place by teaching in secondary school for people older than 25 years of both sexes and teaching in primary school for the younger than 25 years. These findings announce changes in occupational trends in sports, to be taken into account in the framework of the European higher education (Degree of Science in Sport and Physical Activity, own US Masters and Official, lifelong learning programs...).